Assessing the stability of credit ratings - Carvalho, P.; Laux, P.; Pereira, J. (IFABS 2014 Conference, 2014)
The quasi-regulatory role of credit ratings depends on the extent to which they are stable and reflect a through-the-cycle credit risk assessment. Introducing a new measure of rating dynamics summarizing all observed rating transitions, this paper examines if corporate ratings from the three major agencies fulfil such requirement. Changes in ratings are found to be greater around recessions, with Standard & Poor’s being more sensitive than Moody’s and Fitch to the conditions of the business cycle. Despite this sensitiveness to the business cycle, ratings remain a less volatile, though potentially less accurate, measure of credit risk than accounting-based models of default prediction.